2020
DOI: 10.1109/tcomm.2020.3008402
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Intelligent Surface Assisted Two–Way Communications: Performance Analysis and Optimization

Abstract: In this paper, we investigate the two-way communication between two users assisted by a re-configurable intelligent surface (RIS). The scheme that two users communicate simultaneously in the same time slot over Rayleigh fading channels is considered. The channels between the two users and RIS can either be reciprocal or non-reciprocal. For reciprocal channels, we determine the optimal phases at the RIS to maximize the signal-to-interference-plus-noise ratio (SINR). We then derive exact closed-form expressions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(57 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Suppose that the channel state information (CSI) over the links related to IRS is perfectly available. In practice, CSI can be acquired by channel estimation technique [23].…”
Section: System and Channel Model A System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppose that the channel state information (CSI) over the links related to IRS is perfectly available. In practice, CSI can be acquired by channel estimation technique [23].…”
Section: System and Channel Model A System Modelmentioning
confidence: 99%
“…where w i , i ∈ {1, 2}, is the self-interference signal modelled as w i ∼ CN(0, σ 2 wi ). Furthermore, the variance of the SI can be modelled as σ 2 wi = t i P i v i [23], [35], where the range of two parameters is t i > 0 and…”
Section: System and Channel Model A System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis conducted by Zhang et al further demonstrated the influence of limited phase shifts on achievable performance levels [ 8 ]. Outage probability and spectral efficiency have also been deduced in multiple-element IRS-assisted systems [ 9 ]. In addition, Boulogeorgos et al compared the outage probability and ergodic capacity of IRS-assisted and amplify-and-forward (AF) relaying wireless systems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [9][10][11][12], RIS-aided systems and relay systems were compared. An RIS requires low-complexity electronic circuits and does not need power amplifiers, mixers, and DACs/ADCs as do relays.…”
mentioning
confidence: 99%